Practical methods of gender identification in Kashmir geese - HAMADANI, HENNA; KHAN, AZMAT ALAM; HAMADANI, AMBREEN; RAFIQ, ANDLEEB (The Indian Journal of Animal Sciences, 2017)
A study was conducted to determine a practical method for gender identification in Kashmir geese and results revealed that it could be carried out by various methods like differentiating by vocalization, visualization of copulatory organ, and differentiating by morphology and behavior. It was established that examination of external genitalia was the most reliable method (100% accuracy), however in view of being cumbersome and requirement for handling of birds, vocalization method with high adoption rate (86.61%) could be the best practical method under field-conditions especially in large flocks.